NATIONAL ARCHITECTURE OF UZBEKISTAN AND ARCHITECTURAL MONUMENTS OF THE INDEPENDENCE PERIOD - Ismonov, Xurshidbek Baxtiyorovich; Raxmonov , Saydullo Murodjon o‘g‘li (Educational Research in Universal Sciences, 2023)
The article contains some information about the building of the first home in the world of the first world, the development of the consciousness of the people and the building of the sobstvennyh home from the first world, clay, brick and tomu podobogo. Predstavleny razlichnye drevneyshie memory art, discovered in the district, and historical architectural memory of the Togo period. More and more, ith the honor of independence, we can see that the national architecture is more developed, the construction of new modern denmarks is more developed. And at the same time we see that historical buildings are being restored. A number of decrees and resolutions of the President of the Republic of Azerbaijan provided information on the construction of modern houses, the restoration of old houses and the construction of new colleges and lyceums. And at the same time, some information is given about the construction of railroads between neighboring countries. In the article, much attention was paid to the issues of architecture and urban planning. It is shown that after gaining independence, the construction of memorial buildings in the national style is getting more and more developed.